Re-imagining One Health: A perspective from social science - Maria Knight Lapinski; Matthew Seeger; Deanna Sellnow; Timothy Sellnow; Teresa L. Thompson (Mètode Science Studies Journal: Annual Review)
One Health is a framework focusing on the dynamic intersections between humans, animals, and ecosystems regarding health systems and practices. As human decisions and actions are the locus of One Health challenges, it is critical to understand how people perceive and act on these connections. Fundamentally, the literature in this area is based in the natural and health sciences; further efforts are still necessary to fully realize the potential of bringing social research squarely into One Health. We suggest several areas of scholarship that could move this effort forward.